The impossibility of informationally efficient markets when forecasts are self-defeating - Christoph Siemroth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
A policy maker (PM) needs information that only financial market traders know in order to implement his optimal policy, and traders may aggregate this information in asset prices. In such a setting, prices can become uninformative, because the PM reacts to information contained in prices, thereby changing asset values and possibly punishing traders for revealing the information. I derive a necessary and sufficient condition for the possibility of fully revealing and accurate prices in large financial markets. Non-fulfillment of this condition means prices cannot be informationally efficient. The condition is also necessary and sufficient for the existence of fully revealing REE, and explains results from several applications in the literature. The condition implies that assets whose values are invertible in the underlying are superior in terms of information revelation compared to assets whose values are non-invertible.
Keywords: D84; G10; D53; 330